A modified fluoropolymer binder and its preparation method and application
By grafting and modifying the fluoropolymer binder P (VDF-CTFE) to build a hydrogen bond network, the problems of degumming, cracking and long-term creeping of fluoropolymer-based binder explosives during transportation and storage are solved, and the significant mechanical performance improvement of the binder composite material is achieved.
Patent Information
- Application Number
- CN202211302423.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-10-24
AI Technical Summary
Fluoropolymer-based bonded explosives are prone to problems such as degumming, cracking, and long-term creep during transportation and storage, and the prior art is difficult to effectively solve these problems.
By grafting the fluoropolymer binder P (VDF-CTFE), a thiol-ene addition reaction is used to graft thiol-ene addition reaction to graft thiol-containing hydrogen bonding units such as hydroxyl groups and amino groups to build a hydrogen bond network and improve the bonding performance.
The modified binder composite material exhibits significantly improved mechanical properties, including the improvement of indicators such as tensile strength, tensile modulus, and elongation of breakage. The fracture strength is increased by about 280%, the tensile modulus is increased by about 78%, and the fracture growth rate is increased by 180%.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer binders, and in particular relates to a modified fluoropolymer binder and a preparation method and application thereof. Background Art
[0002] Polymer bonded explosives (PBX) are a type of high-energy composite materials with high energy density, excellent mechanical properties and high safety performance. They are widely used in high-power conventional weapons warheads and nuclear warheads. PBX can be divided into press-type explosives, cast thermosetting explosives, flexible explosives and other types. Among them, press-type explosives have the highest energy density and are the most widely used type. They usually contain high-energy explosives (93%-90%wt), polymer binders, plasticizers, insensitivity agents and other components. Fluororubber has a high adhesion work with commonly used explosive crystals (such as TATB, HMX) due to its high density, high thermal stability, chemical inertness and aging resistance. As a binder, it is widely used in high-performance combat PBX at home and abroad. Although fluoropolymers have shown excellent performance in PBX explosives, with the upgrading and replacement of modern weapons and equipment, fluoropolymer-based bonded explosives have problems such as debonding, cracking, and long-term creep during transportation and storage. Nowadays, higher requirements are placed on the performance of fluoropolymer-based explosive binders. Summary of the invention
[0003] In view of the problems of degumming, cracking, long-term creep and the like of fluoropolymer-based adhesive explosives in the transportation and storage in the above-mentioned prior art, the purpose of the present invention is to design and provide a modified P (VDF-CTFE) adhesive based on hydrogen bond reinforcement and its preparation method and application. The present invention grafts and modifies the fluoropolymer adhesive P (VDF-CTFE), and uses a thiol-ene addition reaction to graft mercapto compounds containing hydrogen bond building units such as hydroxyl and amino groups in a one-step method, so as to build a hydrogen bond network between polymer chains and between the adhesive and the composite material, thereby improving the adhesive performance of the adhesive. The adhesive is compounded with melamine (PBX explosive crystal simulant) by a solvent method and hot pressing to form dumbbell-shaped and small-charge column samples, and the samples compounded with the modified adhesive show high mechanical properties.
[0004] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is:
[0005] In one aspect, the present invention provides a method for preparing a modified fluoropolymer binder, comprising the following steps:
[0006] (1) Weigh polyvinylidene fluoride-chlorotrifluoroethylene (VDF-CTFE), add N,N-dimethylformamide or a mixture of N,N-dimethylformamide and tetrahydrofuran as a solvent, add a catalyst and a grafting monomer after fully dissolving, stir and react, wash and precipitate the obtained polymer solution with dilute hydrochloric acid, remove excess alkali, filter and dry in an oven to obtain a product;
[0007] (2) The product obtained after drying in step (1) is dissolved in ethyl acetate, precipitated in water for 2-3 times, and then dried in an oven to obtain a P(VDF-CTFE)-g-ME binder (i.e., polyvinylidene fluoride-chlorotrifluoroethylene grafted mercaptoethanol binder).
[0008] The modified fluoropolymer binder, wherein the catalyst in step (1) is an alkaline compound, preferably the catalyst is (triethylamine (TEA), tri-n-butylamine (TnBA), methylamine (HMTA), n-hexylamine (HexAM)) dipropylamine (DnPA); the grafting monomer includes 2-mercaptoethanol (ME), mercaptoethylamine (MEA), 3-mercapto-1-propanol, 1-mercapto-2-propanol, 2-mercaptobenzyl alcohol, 3-mercapto-1,2-propylene glycol, and mercaptophenol.
[0009] The modified fluoropolymer binder is prepared in step (1), wherein the stirring time is 12 to 24 hours, the reaction temperature is 45 to 55° C., the concentration of the dilute hydrochloric acid is 0.01 mol / L, and the oven temperature is 50° C.
[0010] The modified fluoropolymer binder comprises: in step (1), the molar ratio of polyvinylidene fluoride-chlorotrifluoroethylene, grafting monomer and catalyst is 50-200:3-150:2-9; and the volume ratio of N,N-dimethylformamide to tetrahydrofuran in the mixture of N,N-dimethylformamide and tetrahydrofuran is 1:1.
[0011] The modified fluoropolymer binder described above has a molar composition of polyvinylidene fluoride-chlorotrifluoroethylene in step (1) as follows: a molar ratio of vinylidene fluoride to chlorotrifluoroethylene of 1:1 to 4.
[0012] The modified fluoropolymer binder, the molar composition of the polyvinylidene fluoride-chlorotrifluoroethylene is: when the molar ratio of vinylidene fluoride to chlorotrifluoroethylene is 1:1, it is referred to as F2311, and the solvent is N,N-dimethylformamide; when the molar composition of the polyvinylidene fluoride-chlorotrifluoroethylene is: when the molar ratio of vinylidene fluoride to chlorotrifluoroethylene is 1:4, it is referred to as F2314, and the solvent is a mixture of N,N-dimethylformamide and tetrahydrofuran. Because the proportion of monomers in P(VDF-CTFE) is different, the solubility will change. When the solubility is good, N,N-dimethylformamide is used as a solvent, and when the solubility is poor, a mixed solvent of N,N-dimethylformamide and tetrahydrofuran is needed.
[0013] The modified fluoropolymer binder described above, wherein the temperature of the oven in step (2) is 45-55°C.
[0014] In a second aspect, the present invention provides a modified fluoropolymer binder prepared by any one of the preparation methods described above.
[0015] In a third aspect, the present invention provides the use of the modified fluoropolymer binder as a binder for polymer bonded explosives.
[0016] The method of the invention uses N,N-dimethylformamide or a mixture of N,N-dimethylformamide and tetrahydrofuran as a solvent, weak base triethylamine as a catalyst, and P(VDF-CTFE) as a raw material to synthesize the modified product P(VDF-CTFE)-g-ME in one step.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The P(VDF-CTFE)-g-ME binder of the present invention exhibits excellent mechanical properties in the compounding with the explosive crystal simulant melamine. The tensile strength, tensile modulus and elongation at break of the explosive simulant compounded with the P(VDF-CTFE)-g-ME binder are greatly improved, the breaking strength can be increased by up to about 280%, the tensile modulus can be increased by up to about 78%, and the breaking growth rate can be increased by up to 180%. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the reaction equation in step 1 of Example 1;
[0020] Figure 2 The raw material P (VDF-CTFE) (50 / 50) before and after modification of the binder 1 H-NMR curve;
[0021] Figure 3 DSC curves of the binder before and after modification of the raw material P(VDF-CTFE)(50 / 50);
[0022] Figure 4 The TGA curves of the binder before and after modification of the raw material P(VDF-CTFE)(50 / 50);
[0023] Figure 5 The tensile curves of melamine, a binder composite explosive simulant, before and after modification of the raw material P(VDF-CTFE)(50 / 50);
[0024] Figure 6 Compression curves of melamine, a binder composite explosive simulant, before and after modification of the raw material P(VDF-CTFE)(50 / 50).
[0025] Figure 7 The binder before and after modification of P(VDF-CTFE)(20 / 80) 1 H-NMR curve;
[0026] Figure 8 DSC curves of the binder before and after P(VDF-CTFE)(20 / 80) modification;
[0027] Fig. 9 TGA curves of the binder before and after P(VDF-CTFE)(20 / 80) modification;
[0028] Fig.10 The tensile curves of melamine, a binder composite explosive simulant, before and after modification of P(VDF-CTFE)(20 / 80);
[0029] Fig.11 Compression curves of melamine, a binder composite explosive simulant, before and after modification with P(VDF-CTFE)(20 / 80). DETAILED DESCRIPTION
[0030] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0031] Embodiment 1:
[0032] The preparation method of the modified P(VDF-CTFE)(50 / 50), namely P(VDF-CTFE)-g-ME, comprises the following steps:
[0033] Step 1: Add raw material P (VDF-CTFE) (50 / 50) into the reaction bottle, that is, the molar composition of raw material P (VDF-CTFE) is VDF: CTFE = 1: 1, and add solvent N, N-dimethylformamide. After fully dissolved, add catalyst triethylamine and monomer 2-mercaptoethanol, wherein the molar ratio of raw material P (VDF-CTFE) to monomer 2-mercaptoethanol and catalyst triethylamine is 100:50:3, and stir and react at 55°C for 24 hours. The obtained polymer solution is washed and precipitated in 0.01 mol / L dilute hydrochloric acid solution, and the excess triethylamine is removed at the same time. The obtained polymer is filtered and dried in an oven at 50°C. The reaction equation is as follows Figure 1 shown.
[0034] Step 2: After drying, the product was dissolved in ethyl acetate, chromatographed in water to reduce impurities, repeated twice, and finally dried in an oven at 50°C to obtain a modified product of the P(VDF-CTFE) (50 / 50) binder. The raw material P(VDF-CTFE) (50 / 50) and the modified product were characterized by hydrogen nuclear magnetic resonance spectroscopy. The results are as follows: Figure 2 As shown in the figure, the modified product P(VDF-CTFE)-g-ME has new peaks at 3.6-3.9ppm and 3.1ppm compared with the raw material P(VDF-CTFE)(50 / 50), and these two peaks correspond to the chemical shift of H on the carbon atom of 2-mercaptoethanol (SH-CH2-CH2OH). The graft molar content in the P(VDF-CTFE) modified binder measured by nuclear magnetic resonance is 1.8%.
[0035] Performance test of modified P(VDF-CTFE)-g-ME binder composite explosive simulant melamine:
[0036] 1. Dissolve 2g of the modified product in 20mL of ethyl acetate solvent, add 18g of melamine to the solution, stretch (compress) the sample, the mass ratio of the binder in the composite material is 10% or 5%, ultrasonicate for 10min for dispersion, and stir until the solvent evaporates completely.
[0037] 2. Put the composite material of adhesive and melamine from which the solvent has evaporated completely into a mold and heat-press it into the required test specimen.
[0038] Embodiment 2:
[0039] Step 1: Add raw material P (VDF-CTFE) (50 / 50) to the reaction bottle, and add solvent N, N-dimethylformamide at the same time. After fully dissolving, add catalyst triethylamine and monomer 2-mercaptoethanol, wherein the molar ratio of raw material P (VDF-CTFE) to monomer 2-mercaptoethanol and catalyst triethylamine is 200:150:9, and stir the reaction at 55°C for 24 hours. The obtained polymer solution is washed and precipitated in 0.01mol / L dilute hydrochloric acid solution, and the excess triethylamine is removed at the same time. The obtained polymer is filtered and dried in an oven at 50°C.
[0040] Step 2: After drying, the product was dissolved in ethyl acetate and precipitated in water to reduce impurities, which was repeated twice and finally dried in an oven at 50°C to obtain a modified product of the P(VDF-CTFE) (50 / 50) binder. The raw material and the modified product were characterized by hydrogen nuclear magnetic resonance spectroscopy. The results are as follows: Figure 2 As shown, P(VDF-CTFE)-g-ME has new peaks at 3.6-3.9ppm and 3.1ppm compared with the raw material, which correspond to the chemical shift of H on the carbon atom of 2-mercaptoethanol (SH-CH2-CH2OH). The molar content of P(VDF-CTFE) in the modified binder was 3.5% by NMR.
[0041] Performance test of modified P(VDF-CTFE)-g-ME binder composite explosive simulant melamine:
[0042] 1. Dissolve 2g of the modified product in 20mL of ethyl acetate solvent, add 18g of melamine to the solution, stretch (compress) the sample, the mass ratio of the binder in the composite material is 10% or 3%, ultrasonicate for 10min for dispersion, and stir until the solvent evaporates completely.
[0043] 2. Put the composite material of adhesive and melamine from which the solvent has evaporated completely into a mold and heat-press it into the required test specimen.
[0044] Table 1 below shows the performance test results of 10% adhesive compounded with melamine; Table 2 shows the performance test results of 3% adhesive compounded with melamine.
[0045] Table 110% adhesive composite melamine performance test results
[0046]
[0047] Table 23% adhesive composite melamine performance test results
[0048]
[0049] The performance test results of the modified binder composite explosive simulant melamine of Examples 1 and 2 are as follows: Figure 3-6 As shown, Figure 3 The DSC curve results show that the glass transition temperature of the modified binder is T g It increases with the increase of grafting amount. Figure 4 The TGA curve results show that the grafted side chains of the modified binder break and decompose at about 200°C. Figure 5 The results of the tensile stress-strain curve of 10% adhesive composite melamine show that within a certain grafting range of the modified adhesive, with the increase of grafting content, the tensile strength, tensile modulus and elongation at break of the adhesive composite material are greatly improved. The breaking strength can be increased by up to about 280%, the tensile modulus can be increased by up to about 78%, and the breaking growth rate can be increased by up to 180%. Figure 6 The results of the compressive stress-strain curve of 3% adhesive composite melamine show that within a certain grafting range of the modified adhesive, the compressive strength of the adhesive composite material is greatly improved with the increase of the grafting content.
[0050] Embodiment 3:
[0051] Step 1: Add raw material P (VDF-CTFE) (20 / 80) into the reaction bottle, wherein the molar composition of raw material P (VDF-CTFE) is VDF: CTFE = 1: 4, and add solvent N, N-dimethylformamide and tetrahydrofuran (volume ratio 1: 1) at the same time. After fully dissolved, add catalyst triethylamine and monomer 2-mercaptoethanol, wherein the molar ratio of raw material P (VDF-CTFE) (20 / 80) to monomer 2-mercaptoethanol and catalyst triethylamine is 50: 6: 3, and stir the reaction at 55°C for 24 hours. The obtained polymer solution is washed and precipitated in 0.01 mol / L dilute hydrochloric acid solution, and the excess triethylamine is removed at the same time. The obtained polymer is filtered and dried in an oven at 50°C.
[0052] Step 2: After drying, the product was dissolved in ethyl acetate and precipitated in water to reduce impurities, which was repeated twice and finally dried in an oven at 50°C to obtain a modified product of the P(VDF-CTFE) (20 / 80) binder. The raw material and the modified product were characterized by hydrogen nuclear magnetic resonance spectroscopy. The results are as follows: Figure 7 As shown in the figure, P(VDF-CTFE)(20 / 80)-g-ME has new peaks at 3.6-3.9ppm and 3.1ppm compared with the raw material, and these two peaks correspond to the chemical shift of H on the carbon atom of 2-mercaptoethanol (SH-CH2-CH2OH). The molar content of P(VDF-CTFE) in the modified binder is 0.6% as measured by NMR.
[0053] Performance test of modified P(VDF-CTFE)(20 / 80)-g-ME binder composite explosive simulant melamine:
[0054] 1: Dissolve 2g of the modified product in 20mL of ethyl acetate solvent, add 18g of melamine to the solution, stretch (compress) the sample so that the mass ratio of the binder in the composite material is 10% or 3%, ultrasonicate for 10min for dispersion, and stir until the solvent evaporates completely.
[0055] 2: Put the composite material of adhesive and melamine from which the solvent has evaporated completely into a mold and hot-press it into the required test specimen.
[0056] Embodiment 4:
[0057] Step 1: Add raw material P (VDF-CTFE) (20 / 80) to the reaction bottle, wherein the molar composition of raw material P (VDF-CTFE) is VDF: CTFE = 1: 4, and add solvent N, N-dimethylformamide and tetrahydrofuran (volume ratio 1: 1) at the same time. After fully dissolved, add catalyst triethylamine and monomer 2-mercaptoethanol, wherein the molar ratio of raw material P (VDF-CTFE) (20 / 80) to monomer 3-mercapto 1-propanol and catalyst triethylamine is 50: 3: 2, and stir the reaction at 55°C for 24 hours. The obtained polymer solution is washed and precipitated in 0.01 mol / L dilute hydrochloric acid solution, and the excess triethylamine is removed at the same time. The obtained polymer is filtered and dried in an oven at 50°C.
[0058] Step 2: After drying, the product was dissolved in ethyl acetate and precipitated in water to reduce impurities, which was repeated twice and finally dried in an oven at 50°C to obtain a modified product of the P(VDF-CTFE) (20 / 80) binder. The raw material and the modified product were characterized by hydrogen nuclear magnetic resonance spectroscopy. The results are as follows: Figure 7 As shown in the figure, P(VDF-CTFE)(20 / 80)-g-ME has new peaks at 3.6-3.9ppm and 3.1ppm compared with the raw material, and these two peaks correspond to the chemical shift of H on the carbon atom of 2-mercaptoethanol (SH-CH2-CH2OH). The molar content of P(VDF-CTFE) in the modified binder is 1% as measured by NMR.
[0059] Performance test of modified P(VDF-CTFE)(20 / 80)-g-ME binder composite explosive simulant melamine:
[0060] Step 1: Dissolve 2 g of the modified product in 20 mL of ethyl acetate solvent, add 18 g of melamine to the solution, and stretch (compress) the sample. The mass ratio of the binder in the composite material is 10% (5%). Ultrasonicate for 10 minutes for dispersion and stir until the solvent evaporates completely.
[0061] Step 2: Put the composite material of adhesive and melamine from which the solvent has been completely evaporated into a mold, and heat-press it into the required test specimen.
[0062] Table 3 below shows the performance test results of 10% adhesive compounded with melamine; Table 4 shows the performance test results of 3% adhesive compounded with melamine.
[0063] Table 3 Performance test results of 10% adhesive compound melamine
[0064]
[0065] Table 4 Performance test results of 3% adhesive composite melamine
[0066]
[0067] The performance test results of the modified binder composite explosive simulant melamine of Examples 3 and 4 are as follows: Figure 8-11 As shown, Figure 8 The DSC curve results show that the glass transition temperature of the modified binder is T g It decreases with the increase of grafting amount. Fig. 9 The TGA curve results show that the grafted side chains of the modified binder break and decompose at around 160°C. Fig.10 The tensile stress-strain curve results of 10% adhesive composite melamine show that within a certain grafting range of the modified adhesive, with the increase of grafting content, the tensile strength and elongation at break of the adhesive composite material are improved, with the tensile strength increased by up to about 90% and the elongation at break increased by up to about 70%. Fig.11 The results of the compressive stress-strain curve of 3% adhesive composite melamine show that within a certain grafting range of the modified adhesive, the compressive strength of the adhesive composite material is greatly improved with the increase of the grafting content.
Claims
1. A method for preparing a modified fluoropolymer binder as a binder for polymer bonded explosives, characterized in that: The following steps are involved: (1) Weigh polyvinylidene fluoride-chlorotrifluoroethylene, add N,N-dimethylformamide or a mixture of N,N-dimethylformamide and tetrahydrofuran as a solvent, add a catalyst and a grafting monomer after fully dissolving, stir and react, wash and precipitate the obtained polymer solution with dilute hydrochloric acid, filter and dry in an oven to obtain a product; The grafting monomer is 2-mercaptoethanol, mercaptoethylamine, 3-mercapto-1-propanol, 1-mercapto-2-propanol, 2-mercaptobenzyl alcohol, 3-mercapto-1,2-propylene glycol or mercaptophenol; (2) The product obtained after drying in step (1) is dissolved in ethyl acetate, precipitated in water for 2-3 times, and then dried in an oven to obtain a P(VDF-CTFE)-g-ME binder.
2. The preparation method according to claim 1, characterized in that The catalyst in step (1) is a base compound.
3. The preparation method according to claim 1, characterized in that: The catalyst in step (1) is triethylamine, tri-n-butylamine, methylamine, n-hexylamine or dipropylamine.
4. The preparation method according to claim 1, characterized in that: The stirring reaction time in step (1) is 12 to 24 hours, the stirring reaction temperature is 50 to 60° C., the concentration of dilute hydrochloric acid is 0.01 mol / L, and the temperature of the oven is 45 to 55° C.
5. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of polyvinylidene fluoride-chlorotrifluoroethylene, grafting monomer and catalyst is 50-200:3-150:2-9, and the volume ratio of N,N-dimethylformamide to tetrahydrofuran in the mixture of N,N-dimethylformamide and tetrahydrofuran is 1:
1.
6. The preparation method according to claim 1, characterized in that: The molar composition of polyvinylidene fluoride-chlorotrifluoroethylene in the step (1) is: the molar ratio of vinylidene fluoride to chlorotrifluoroethylene is 1:1-4.
7. The preparation method according to claim 6, characterized in that: The molar composition of the polyvinylidene fluoride-chlorotrifluoroethylene is: when the molar ratio of vinylidene fluoride to chlorotrifluoroethylene is 1:1, the solvent is N,N-dimethylformamide; when the molar composition of the polyvinylidene fluoride-chlorotrifluoroethylene is: when the molar ratio of vinylidene fluoride to chlorotrifluoroethylene is 1:4, the solvent is a mixture of N,N-dimethylformamide and tetrahydrofuran.
8. The preparation method according to claim 1, characterized in that: The temperature of the oven in step (2) is 45-55°C.
9. A modified fluoropolymer binder, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the modified fluoropolymer binder according to claim 9 as a binder for polymer bonded explosives.
Citation Information
Patent Citations
Perfluor dioxole-modified fluorine-containing polymer
CN104448097A
Method for preparing P(VDF-DB)-g-S-C3H6-SO3H proton exchange membrane material
CN107556422A